Gamificação na produção textual de fotorreportagens: engajamento e proficiência - Silva , Erivania Lima da (2023)
Low proficiency and engagement in the practice of writing in the school context still represent a problem, since many of the students demonstrate disinterest and many difficulties in the development of textual production activities. In view of the above, the study on screen had the general objective of understanding the gamification process applied to education, especially in the development of written production, based on the discursive/textual photojournalism genre. For this, it developed the following specific objectives: to discuss the conceptions of active methodologies, gamification and writing; promote diagnostic activities on students' textual production; develop and apply gamified learning activities, observing their applicability for written textual production and student engagement; produce a pedagogical notebook, based on the gamified learning experience with a focus on the development of writing, to be disseminated in physical and interactive support, to support other Portuguese language teachers. The research had as participants, students of the 6th year of Elementary School and presented a qualitative and ethnographic approach. The field work took place in an interventionist way, through action research, and used bibliographical research, participant observation, the ethnographic process and the didactic sequence as instruments/procedures that generated data. The discursive/textual genre that structured the corpus of the research was photojournalism, as it is provided for in the National Common Curricular Base (BNCC). The present study is organized in three thematic axes, anchored in several authors, namely: Active methodologies - Berbel (2011), Silva et al (2017), Bertini (2017), Moran (2018) and Souza (2020); gamification - Vianna et al (2013), Alves (2015), Burke (2015), Bussarello (2016, 2017) and Eugenio (2020); writing - Peregrino (1991), Bazerman (2006), Ribeiro (2018), Medeiros (2017) and Boroski (2020), among others; discursive/textual genres - Bakhtin (1992), Marcuschi (2008). Data analysis was performed using the method of content analysis systematized in Bardin (2011). After applying the gamified didactic sequence and after analyzing the generated data, the objectives of the study were achieved and from the results generated it can be seen that the use of contemporary technological resources and the adoption of gamified strategies in the face of traditional contexts positively impacts the proficiency and engagement of students in writing activities and apprehension of the photojournalism genre, a genre that needs to be further explored in elementary school, considering its discursive, textual and social circulation potential, in addition, it should be noted that when gamifying it is essential to have a plan well-structured and caution, as excesses can be harmful. It is concluded, therefore, that gamification applied to education and in particular, in Portuguese language classes, is an active methodology that maximizes results. Its applicability is viable and beneficial to the teaching and learning process, as long as it is well planned and executed.